The Typewriter’s Tale: Re-Exploring the Historical Figure of Henry James through Fiction - Breytenbach, Albertus (Journal of Literary Studies)
This article investigates the relationship between historical fiction, history, and the portrayal of the character and identity of Henry James with specific reference to The Typewriter’s Tale (2005) by Michiel Heyns. Furthermore, it explores how Heyns proceeds to strike a historically responsible balance in his portrayal of the identities of Henry James, Morton Fullerton and Edith Wharton as characters in the novel and the identities of these personae as historical figures. It also explores how Heyns imaginatively bridges the gaps in the historical record or relies on creative licence to reinterpret events and characters. Lastly, the contribution that historical fiction can make to our understanding of the identity and character of historical figures is considered.